Problems with Mortgage Rights on Inherited Property - Frida Nurrahma Masturi; Asep Herlan; Al Fiani Nenden Iryatin (Judge : Jurnal Hukum, 2025)
The increasing economic activity, particularly in the banking sector, has led to land being frequently used as the primary guarantee in credit agreements through mortgage rights (hak tanggungan). However, problems arise when the debtor passes away and the mortgaged land becomes part of the inheritance. Since mortgage rights are characterized by the droit de suite principle, the right remains attached to the land regardless of changes in proprietary rights. This legal characteristic often leads to conflicts between creditors and heirs, especially when the heirs were not involved in or unaware of the original credit agreement. Meanwhile, banking institutions require legal certainty over guarantee to exercise their execution rights effectively. This research aims to identify the legal convergence between inheritance rights and mortgage rights in order to uphold justice and legal certainty for all parties involved. The study adopts a normative juridical approach, using secondary data derived from statutory regulations and legal literature. The findings reveal that the lack of synchronization between inheritance law and security law creates legal uncertainty and practical problems, which can only be resolved through regulatory harmonization and procedural clarity in guarantee execution involving inherited land